Optimal income taxation and public goods provision in a large economy with aggregate uncertainty - Felix Bierbrauer (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study a large economy model in which individuals have private information about their productive abilities and their preferences. Moreover, there is aggregate uncertainty so that the social benefits from taxation and public goods provision are a priori unknown. The analysis is based on a mechanism design approach that imposes a requirement of robustness with respect to individual beliefs and a requirement of coalition-proofness. The paper provides a tractable and intuitive characterization of incentive-feasible tax and expenditure policies: Incentive constraints associated with productive abilities reflect only individual behavior, whereas those associated with public goods preferences reflect only collective behavior.
Keywords: D71; D82; H21; H41; 330; optimal taxation; public goods provision; revelation of preferences; robust mechanism design; Optimale Besteuerung; Öffentliches Gut; Mechanism; Offenbarte Präferenzen; Theorie